Bisecting Real and Fake Body Parts: Effects of Prism Adaptation After Right Brain Damage - Bolognini, Nadia; Casanova, Debora; Maravita, Angelo; Vallar, Giuseppe (Frontiers in Human Neuroscience, 2012)
The representation of body parts holds a special status in the brain, due to their prototypical shape and the contribution of multisensory (visual and somatosensory-proprioceptive) information. In a previous study (Sposito et al., 2010), we showed that patients with left unilateral spatial neglect exhibit a rightward bias in setting the mid-point of their left forearm, which becomes larger when bisecting a cylindrical object comparable in size. This body part advantage, found also in control participants, suggests partly different processes for computing the extent of body parts and objects. In this study we tested 16 right-brain-damaged patients, and 10 unimpaired participants, on a manual bisection task of their own (real) left forearm, or a size-matched fake forearm. We then explored the effects of adaptation to rightward displacing prism exposure, which brings about leftward aftereffects. We found that all participants showed prism adaptation and aftereffects, with right-brain-damaged patients exhibiting a reduction of the rightward bias for both real and fake forearm, with no overall differences between them. Second, correlation analyses highlighted the role of visual and proprioceptive information for the metrics of body parts. Third, single-patient analyses showed dissociations between real and fake forearm bisections, and the effects of prism adaptation, as well as a more frequent impairment with fake body parts. In sum, the rightward bias shown by right-brain-damaged patients in bisecting body parts is reduced by prism exposure, as other components of the neglect syndrome; discrete spatial representations for real and fake body parts, for which visual and proprioceptive codes play different roles, are likely to exist. Multisensory information seems to render self bodily segments more resistant to the disruption brought about by right-hemisphere injury.